Data collection method of wireless sensor network based on mobile robots - WANG Fang; HU Yu (Gong-kuang zidonghua, 2013)
In sparse wireless sensor network, neighboring nodes are far away from each other. The requirement of direct communication among sensor nodes in traditional static data collection methods causes large time-delay and high energy consumption. In order to solve above problem, the paper proposed a data collection method of wireless sensor networks based on mobile robots. The method firstly takes a mobile robot as cluster head node which is nearest to a static sensor node, then judges node moving according to comparison result between average remainder energy of neighboring nodes detected by mobile robot in a period and average remainder energy of all nodes in the network. The mobile robot moves according to random moving strategy in controlled range. When the mobile robot arrives at a new position, the sensor node renews route and selects a new mobile robot as cluster head. The simulation results showed that the method can reduce time-delay of data transmission and energy consumption of sensor nodes greatly compared with traditional static data collection methods.